Comparing Auditory Brain Stem Responses and Transient Otoacoustic Emissions in Premature Infants with Auditory Developmental Delay: Evidence of Temporary Auditory Neuropathy - Mazaheryazdi, Malihah; Sharafi, Mohammad Amin; Akbari, Mehdi; Abolhasan Choobdar, Farhad (Iranian Journal of Child Neurology, 2023)
Objectives Premature birth causes some permanent or temporary abnormalities in the hearing system of the newborn. Inadequate development of the central auditory nervous system and balance, as well as the delay in the formation of the nerve myelin, can be the cause of many hearing disorders, including permanent or temporary auditory neuropathy spectrum disorder (ANSD). The present study aims to identify and understand developmental delay disorder in the hearing system of infants and investigate the possibility of temporary auditory neuropathy in infants. Materials & Methods In this comparative analytical study, twenty premature infants were randomly selected for hearing tests using auditory brainstem response and transient otoacoustic emissions at the time of discharge and three months after the first evaluation. The different components of these tests were analyzed and compared before and after developing the auditory system. Results The OAEs test showed a signal-to-noise ratio above six dB with appropriate amplitudes in all infants. The grand average waveform of the ABR showed a significant difference between the amplitudes of waves III and V before and after maturation in both ears (p<0.05). In addition, the absolute latency of waves, specifically III and V, showed a significant difference between the two assessment times (0.05).